2017
DOI: 10.2166/wst.2017.447
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linked chitosan/marble powder composites for the adsorption of Dimozol Blue

Abstract: Cross-linked chitosan(C)/marble powder (M) composites with different weight ratio percentage (C100M0, C70M30, C50M50, and C30M70) were prepared from marble powder and chitosan and cross-linked using glutaraldehyde. The morphology and the surface area of the chitosan/marble powder composites were also characterized with a scanning electron microscope (SEM) and Micromeritics (ASAP 2020) BET (Brunauer, Emmett and Teller) instrument, respectively. To evaluate the adsorption behaviour of the chitosan/marble powder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…3. It was observed that [30,31]. The absorption band at 1092 cm −1 can be attributed to symmetric stretching of carbonate group.…”
Section: Ftir Analysismentioning
confidence: 98%
“…3. It was observed that [30,31]. The absorption band at 1092 cm −1 can be attributed to symmetric stretching of carbonate group.…”
Section: Ftir Analysismentioning
confidence: 98%